FROM MAIN STREET TO MALL : THE RISE AND FALL OF THE AMERICAN DEPARTMENT STORE - Howard, Vicki, 1965- (American business, politics, and society, 2015)
"The first national study of the department store industry, From Main Street to Mall traces the changing economic and political contexts that transformed the American shopping experience in the twentieth century. With careful attention to small-town stores as well as glamorous landmarks such as Marshall Field's in Chicago and Wanamaker's in Philadelphia, historian Vicki Howard offers a comprehensive account of the uneven trajectory that brought about the loss of locally identified department store firms and the rise of national chains like Macy's and J. C. Penney. She draws on a wealth of primary source evidence to demonstrate how the decisions of consumers, government policy makers, and department store industry leaders culminated in today's Wal-Mart world. Richly illustrated with archival photographs of the nation's beloved downtown business centers, From Main Street to Mall shows that department stores were more than just places to shop." -- Book jacket